Arbuscular mycorrhizal fungi in soil aggregates from fields of “murundus” converted to agriculture - Carneiro, Marco Aurélio Carbone; Ferreira, Dorotéia Alves; Sousa, Edicarlos Damacena de; Paulino, Helder Barbosa; Saggin Junior, Orivaldo José; Siqueira, José Oswaldo (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the spore density and diversity of arbuscular mycorrhizal fungi (AMF) in soil aggregates from fields of “murundus” (large mounds of soil) in areas converted and not converted to agriculture. The experiment was conducted in a completely randomized design with five replicates, in a 5x3 factorial arrangement: five areas and three aggregate classes (macro‑, meso‑, and microaggregates). The evaluated variables were: spore density and diversity of AMF, total glomalin, total organic carbon (TOC), total extraradical mycelium (TEM), and geometric mean diameter (GMD) of soil aggregates. A total of 21 AMF species was identified. Spore density varied from 29 to 606 spores per 50 mL of soil and was higher in microaggregates and in the area with 6 years of conversion to agriculture. Total glomalin was higher between murundus in all studied aggregate classes. The area with 6 years showed lower concentration of TOC in macroaggregates (8.6 g kg-1) and in microaggregates (10.1 g kg-1). TEM was greater at the top of the murundus in all aggregate classes. GMD increased with the conversion time to agriculture. The density and diversity of arbuscular mycorrhizal spores change with the conversion of fields of murundus into agriculture.
Keywords: diversity of arbuscular mycorrhizal fungi; geometric mean diameter; total glomalin; total mycelium; total organic carbon